2010
DOI: 10.1103/physrevb.82.184203
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nucleation of solid Al from the melt byTiB2andAl3Ti: Anab initiomolecular dynamics study

Abstract: The nucleation of solid Al from the melt by TiB 2 is well established and is believed to involve the formation of Al 3 Ti. Since the atomic scale mechanisms involved are not fully understood, we look to computer simulation to provide insight. As there is an absence of suitable potentials for all of this complex system we have performed large scale density functional theory molecular dynamics simulations of the nucleation of solid Al from the melt on TiB 2 and Al 3 Ti substrates at undercoolings of around 2K. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The results showed that the liquid Li atoms near the interface were layered, during the simulation duration few Li atoms invaded into the Fe substrate even at 1100K, and also few Fe atoms dissolved in the liquid Li. Previous literatures reported that the interface properties present apparent orientation dependences [10][11][13][14][15][16][17][18], which suggests that to obtain a full view of the interface properties of the Fe-Li solid-liquid interface further work should be done. In this work, the Fe(110)/(111)-Li solid-liquid interfaces are examined and the results are compared with each other as well as with our previous findings, what's more we have illuminated the underlying mechanism of the orientation dependence observed in the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT interface properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the liquid Li atoms near the interface were layered, during the simulation duration few Li atoms invaded into the Fe substrate even at 1100K, and also few Fe atoms dissolved in the liquid Li. Previous literatures reported that the interface properties present apparent orientation dependences [10][11][13][14][15][16][17][18], which suggests that to obtain a full view of the interface properties of the Fe-Li solid-liquid interface further work should be done. In this work, the Fe(110)/(111)-Li solid-liquid interfaces are examined and the results are compared with each other as well as with our previous findings, what's more we have illuminated the underlying mechanism of the orientation dependence observed in the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT interface properties.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Turlo et al [3] simulated the dissolution process of solid Ni in liquid Al and a diffusion-limited dissolution model has been developed. In order to unveil the grain refining mechanism of Al with different refiners, the interfaces between refiners and liquid Al have been extensively investigated [15][16][17][18][19]. The findings have exposed different refining mechanisms of different refiners and the different refining abilities of different crystal planes.…”
Section: Introductionmentioning
confidence: 99%
“…The initial S/L interfacial models for the simulations were prepared using the method proposed by Wang et al [12]. In the first step, the solid substrates were fully relaxed, until the residual forces fell below 0.01 eV/Å; meanwhile, liquid Al was prepared by melting the solid Al (15 × 15 × 15 supercell) in Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) [43] using the embedded atom model (EAM) potential [44].…”
Section: Methodsmentioning
confidence: 99%
“…These ordered structures may manifest as clusters with unique symmetry (such as the well-assumed icosahedral structure [3]) or quasi-layers [4][5][6][7][8][9]. The former mainly occur in the systems absence of inoculation [3] and the latter have frequently been observed near the atomically smooth surfaces [10][11][12][13]. In this work, we focus on the substrate-induced liquid layers, which have been extensively studied in the field of lubrication, epitaxial growth, superhydrophobic materials [6], energy-storage materials [8,14], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of DFT and MD is especially appealing as it allows us to retain an accurate description of the cohesion while including the nuclear dynamics associated with finite temperatures [21,22]. However, it is a computationally expensive approach and for many cases less costly alternatives are necessary.…”
Section: Introductionmentioning
confidence: 99%